Enhancing Accounting Learning Motivation Through Artificial Intelligence Driven Optimization Strategies For Students - Huda, Nurul; Abdurrahman, Abdurrahman; Hidayati, Nurul (Asosiasi Dosen Akuntansi Indonesia, 2023)
This research explores the impact of AI on accounting students' learning motivation, using a quantitative associative causality approach. This research, which involved 31 accounting students at Medan State University, revealed that there was a significant influence of the use of AI on student learning motivation of 61.4%. This study advocates integrating AI into accounting curricula to increase student motivation and prepare them for the demands of the digital era. The remaining 38.6% of factors influencing motivation require further investigation. Overall, these findings emphasize the critical role of AI in shaping educational outcomes in accounting and underscore the importance of technological competency for students in an evolving landscape